2019
DOI: 10.1111/jvim.15544
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐13 and interleukin‐33 mRNA are underexpressed in the duodenal mucosa of German Shepherd dogs with chronic enteropathy

Abstract: Background A recent genome‐wide association study in German Shepherd dogs (GSDs) with chronic enteropathy (CE) has identified polymorphisms in the Th2 cytokine genes. Hypothesis/objective To determine if the expression of the Th2 cytokines, interleukin‐13 (IL‐13) and interleukin‐33 (IL‐33), is altered in the duodenal mucosa of GSDs with CE compared to non‐GSDs with CE and healthy dogs. Animals Twenty client‐owned dogs diagnosed with CE (10 GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In particular, the recent development and availability of RNAScope represented a major improvement over traditional RNA ISH methods that are largely affected by low stability of RNA in the sample ( 43 , 44 ), often resulting in a suboptimal detection of RNA and also in poor reproducibility ( 43 ). In veterinary medicine, the use of RNAScope has begun to emerge, but it is still mainly limited to the detection of specific infectious agents ( 45 , 46 ) or inflammatory cytokines ( 47 ). With the present study, we aimed to experiment and validate the use of RNAScope in detecting and measuring the expression of c-KIT mRNA in formalin fixed and paraffin-embedded (FFPE) canine MCTs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the recent development and availability of RNAScope represented a major improvement over traditional RNA ISH methods that are largely affected by low stability of RNA in the sample ( 43 , 44 ), often resulting in a suboptimal detection of RNA and also in poor reproducibility ( 43 ). In veterinary medicine, the use of RNAScope has begun to emerge, but it is still mainly limited to the detection of specific infectious agents ( 45 , 46 ) or inflammatory cytokines ( 47 ). With the present study, we aimed to experiment and validate the use of RNAScope in detecting and measuring the expression of c-KIT mRNA in formalin fixed and paraffin-embedded (FFPE) canine MCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in CIE dogs failed to detect signature cytokines during chronic enteric inflammation, 31,32 or a Th17 polarization 33,34 as in CD in humans 4 . However, more recent studies in dogs have described differences in the cytokine expression profiles of intestinal epithelial cells in subgroups of dogs with CIEs 35 and show involvement of Th2 cytokines in German Shepherd dog (GSD) enteropathy 36 . Other factors such as polymorphisms in the STAT3 locus as described in humans with CD and UC 37 or single nucleotide polymorphisms in genes encoding cytokines, such as those recently detected in GSD, also could play a role but were not investigated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…8,25 Since canine CE involves various inflammatory cells, such as CD4 + T-cells, CD8 + T-cells, plasma cells, and macrophages, 19 a more detailed understanding of the cytokine interactions between these inflammatory cells is essential for elucidating the pathogenesis of this disease. Previous studies on canine duodenal CE reported decreases in interleukin (IL)-17, IL-13, and IL-33 mRNA expression in German shepherd dogs, 24,45 while others found no significant difference in cytokine mRNA expression patterns between dogs with and without CE. 35,39 Therefore, canine CE is currently considered to be a complex group of diseases involving multiple factors, such as breed, the type of cellular infiltration in the lamina propria, and disease progression.…”
mentioning
confidence: 93%